Macro- and meso- marine debris on beaches in Khanh Hoa Province, Vietnam: density, composition, and pollution indicators - Duong , Thi Lim; Dao, Dinh Cham; Nguyen Thi, Lan Huong; Nguyen, Thi Hue; Dang , Tran Quan; Nguyen Thi, Huong Thuy; Tran , Thu Thuy; Trinh Thi, Minh Trang; Pham, Thi Dung; Dao , Ngoc Nhiem; et al. (Vietnam Journal of Marine Science and Technology, 2023)
Marine debris is a prevalent problem that affects oceans and coastal regions worldwide, particularly beaches. The problem of marine litter pollution is also severe on beaches in Nha Trang. In this study, marine debris with a size ≥ 5 mm was collected at seven locations along the coastline of Nha Trang during both dry and rainy seasons, accruing a total of 4436 items. During the rainy season, most beaches had more debris than that in the dry season, and marine debris density ranged between 0.009 items/m2 to 0.418 items/m2. Results from the beach cleanliness index (CCI) assessment showed that CCI values ranged from 0.2 to 4.4 during the dry season, with beaches classified as either very clean or clean. Meanwhile, during the rainy season, CCI values ranged from 0.36 to 8.35, resulting in beaches being categorized as very clean, clean, or average. The Plastic Abundance Index (PAI) showed that the PAI ranged from 0.004 to 0.061 during the dry season, while during the rainy season, it ranged from 0.006 to 0.118. PAI values for both seasons indicated low levels of plastic debris distribution on the beaches. However, local authorities and managers need to pay attention to potential sources of pollution, such as waste from food service activities in restaurants, ports and unsustainable waste from aquaculture activities.